Generalization of the Brusov–Filatova–Orekhova Theory for the Case of Variable Income - Peter Brusov; Tatiana Filatova (Mathematics, 2022)
To expand the applicability in practice of the modern theory of cost and capital structure, the theory of Brusov–Filatova–Orekhova (BFO), which is valid for companies of arbitrary age, is generalized for the case of variable income. The generalized theory of capital structure can be successfully applied in corporate finance, business valuation, banking, investments, ratings, etc. income. A generalized Brusov–Filatova–Orekhova formula for the weighted average cost of capital, WACC, is derived using a formula in MS Excel, where the role of the discount rate shifts from WACC to WACC–g (here g is the growth rate) for financially dependent companies and k0–g for financially independent companies is shown. A decrease in the real discount rates of WACC–g and k0–g with g ensures an increase in the company’s capitalization with g. The tilt of the equity cost curve, ke(L), increases with g. Since the cost of equity justifies the amount of dividends, this should change the dividend policy of the company. It turns out that for the growth rate g < g*, the tilt of the curve ke(L) becomes negative. This qualitatively new effect, discovered here for the first time, can significantly change the principles of the dividend policy of the company. The obtained results are compared with the results of the MM theory with variable income.